“They don’t feel what I feel”: lived experiences of women accessing comprehensive abortion care in pastoralist communities of Oromia region, Ethiopia: A Phenomenological study - Tolasa Yadate; Abel Negussie; Yohannes Addisu Wondimagegene; Finina Abebe; Niguse Tadele; Yonas Abebe; Assefa Seme (PLoS ONE, 2026)
Background Unsafe abortion is a significant global health concern, contributing to high rates of maternal mortality, particularly in developing countries. Women in pastoralist communities face unique challenges to access comprehensive abortion care (CAC) due to sociocultural, economic, and geographical barriers. This study explores the lived experiences of women in their journey to utilize CAC services in pastoralist communities of the Oromia region, Ethiopia. Methods A phenomenological study was conducted in pastoralist communities of the Oromia region, including the Borana and Guji zones. A total of nine women were interviewed in-depth for their lived experiences in their journey to access the CAC service. All interviews were audio-recorded, transcribed verbatim, translated to English, and coded using Open Code version 4.03 software. Both inductive and deductive thematic analysis were employed to analyze the data. The lived experiences of women in their journey to access CAC services were analyzed under three categories: ‘before’, ‘during’, and ‘after’ utilizing the CAC service. Results Before receiving CAC service, women faced emotional instability, fear, decision-making difficulties, and barriers such as transportation challenges, stigma, and lack of family support. During the service, women reported mixed experiences with healthcare providers, with some receiving supportive care while others reported disrespect and a lack of privacy. Following receiving CAC service, experiences included both relief and satisfaction for some, while others expressed regret and guilt due to cultural and religious beliefs surrounding abortion. Conclusion The study reveals the complex experiences of women in their journey of accessing CAC services in pastoralist communities, worsened by socio-cultural norms, economic hardship, and limited healthcare infrastructure. Addressing the barriers identified, particularly those related to stigma, provider attitudes, and healthcare accessibility, is essential for improving CAC service delivery in these underserved regions.